Exploring The Challenges for Women Trying To Assume Mid and Senior Leadership Positions In Higher Education In Yemen - Al-Monefie, Shaima (AUC Knowledge Fountain, 2023)
Women in higher education have the potential to serve as influential agents of change, impacting the economic and societal growth of their respective countries through acquiring leadership positions. However, in Yemen, female administrators face a range of challenges that hinder their progression into senior leadership positions within higher education institutions. This study shed light on these obstacles by conducting qualitative interviews with female administrators from a university in Northern Yemen. Drawing upon Morales's Academic Resilience Theoretical Framework for women's empowerment, the research examined the interplay of institutional, cultural, educational, and professional barriers and other challenges that prevent women from assuming senior leadership positions in higher education. The study's findings highlighted the impact of the low representation of women leaders in higher education and the absence of communal and familial support on Yemeni women's ability to ascend to senior leadership positions. The study concluded that the institutional and cultural barriers are strong barriers in undermining women's empowerment programs in Yemen. It highlighted the significant role that Yemeni women could play in driving change in the academic sector. It emphasized the importance of empowering and supporting female administrators to advance into senior leadership positions. Keywords: Higher Education, Women Leadership, Yemen